Effects of JPEG2000 data compression on an automated system for detecting clustered microcalcifications in digital mammograms. - Penedo, M.
The functionalities of the JPEG2000 standard have led to its incorporation into digital imaging and communications in medicine (DICOM), which makes this compression method available for medical systems. In this study, we evaluated the compression of mammographic images with JPEG2000 (16:1, 20:1, 40:1, 60.4:1, 80:1, and 106:1) for applications with a computer-aided detection (CAD) system for clusters of microcalcifications. Jackknife free-response receiver operating characteristic (JAFROC) analysis indicated that differences in the detection of clusters of microcalcifications were not statistically significant for uncompressed versus 16:1 (T=-0.7780;p=0.4370),20:1(T=1.0361;p=0.3007), and 40:1 (T=1.6966;p=0.0904); and statistically significant for uncompressed versus 60.4:1 (T=5.8883;p<0.008), 80:1 (T=7.8414;p<0.008), and 106:1 (T=17.5034;p=<0.008). Although there is a small difference in peak signal-to-noise ratio (PSNR) between compression ratios, the true-positive (TP) and false-positive (FP) rates, and the free-response receiver operating characteristic (FROC), figure of merit values considerably decreased from a 60:1 compression ratio. The performance of the CAD system is significantly reduced when using images compressed at ratios greater than 40:1 with JPEG2000 compared to uncompressed images. Mammographic images compressed up to 20:1 provide a percentage of correct detections by our CAD system similar to uncompressed images, regardless of the characteristics of the cluster. Further investigation is required to determine how JPEG2000 affects the detectability of clusters of microcalcifications as a function of their characteristics
Keywords: JPEG2000 standard; Automated system; Clustered microcalcifications detection; Compression ratio; Computer-aided detection system; Data compression; Digital communications; Digital imaging; Digital mammography; Jackknife free-response receiver operating characteristic analysis; Mammographic image compression; Peak signal-to-noise ratio